Poly(3-bromofuran) material with electrochemical energy storage and preparation method and application thereof

By using a mixed solution of boron tetrabutylammonium tetrafluoride and boron trifluoride ether in the electrochemical polymerization solution and reacting with 3-bromofuran and depositing under constant potential polymerization, a poly(3-bromofuran) material with high electrochemical energy storage was successfully prepared, which solved the problems of harsh preparation conditions of the polyfuran materials and poor quality of the finished product in the prior art, and achieved the preparation of high-performance electrode materials.

CN119314813BActive Publication Date: 2025-04-11WEIFANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411854211.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

It is difficult to prepare high-performance polyfuran materials in the prior art, especially during electrochemical polymerization. Due to the weak aromaticity of the furan and the sensitivity to acid, it is easy to trigger a ring-opening reaction, resulting in harsh preparation conditions and poor quality of the finished product.

Method used

Boron tetrabutylammonium tetrafluoride was dissolved in a mixed solution of acetonitrile and boron trifluoride ether and reacted with 3-bromofuran to form an electrochemical polymerization solution, and deposited on the ITO electrode by constant potential polymerization in a one-chamber triode system to control the potential and deposition time to prepare a poly(3-bromofuran) material with electrochemical energy storage.

Benefits of technology

The prepared poly(3-bromofuran) material has good energy storage capacity, electrochemical performance, electron transmission capability and charge and discharge performance. It is suitable for electrode materials of supercapacitors, improving the electrical performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314813B_ABST
    Figure CN119314813B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of conductive materials and their preparation, and specifically relates to poly (3-bromofuran) materials with electrochemical energy storage, and preparation methods and applications thereof. The preparation method of the poly (3-bromofuran) material with electrochemical energy storage described in the present invention comprises the following steps: dissolving tetrabutylammonium boron tetrafluoride in a mixed solution of acetonitrile and boron trifluoride ether, and then adding 3-bromofuran to obtain an electrochemical polymerization solution; in a one-chamber three-electrode system, using an ITO electrode as a working electrode, using a constant potential polymerization method, the electrochemical polymerization solution is deposited on the ITO electrode to obtain a poly (3-bromofuran) material with electrochemical energy storage. The poly (3-bromofuran) material with electrochemical energy storage provided by the present invention has good energy storage capacity, strong electron transmission capacity, and strong charge and discharge performance. The present invention also provides a preparation method thereof, which is simple to operate, and the prepared poly (3-bromofuran) material is applied to the electrode of a capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive materials and their preparation, and particularly relates to a poly (3-bromofuran) material with electrochemical energy storage, a preparation method and an application thereof. Background Art

[0002] With the continuous growth of energy demand and the continuous development of organic electronic technology, the field of energy storage devices is facing new challenges. Researchers are working on the development of energy storage devices with high power and high energy density. Supercapacitors have shown significant advantages in terms of life cycle, capacity and power density. In the current research on supercapacitor electrode materials, conductive polymers (such as polypyrrole, polyaniline, polythiophene, etc.) have been widely used. These conductive polymers have a wide voltage window and excellent electrochemical energy storage capacity. However, among the five-membered heterocyclic polymers, the preparation and practical application of polyfuran are relatively slow compared with polypyrrole and polythiophene. This is mainly due to the fact that it requires harsh polymerization conditions and the molecular structure is prone to ring opening during the polymerization process, resulting in poor moldability and low conductivity (10 -5 -10 -8 S / cm), poor environmental stability and low solubility, which limit the development and application of polyfuran.

[0003] Electrochemical polymerization is widely recognized as an important method for preparing high-quality polymers. Compared with traditional chemical polymerization methods, electrochemical polymerization offers advantages such as simple operation, high yields of conductive polymers, high conductivity, and good processability. However, when preparing polyfuran using electrochemical polymerization, furan is less aromatic than thiophene and is highly acid-sensitive, easily inducing ring-opening reactions. Furthermore, furan has a high oxidation potential of 1.8 V (vs. SCE), which can damage its aromatic structure. Polyfuran prepared in conventional solvents such as acetonitrile exhibits numerous defects in its conjugated structure, and the synthesis conditions are extremely harsh, making it difficult to obtain high-quality polyfuran membranes. In particular, when the furan monomer contains electron-withdrawing groups such as halogens (e.g., F, Cl, Br), the electron cloud density on the furan ring is reduced due to the influence of these electron-withdrawing groups, further increasing the difficulty of preparing high-performance polyfuran derivatives. Therefore, the preparation of high-performance polyfuran membranes has become a major challenge in the electrochemical synthesis of conductive polymers. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a poly (3-bromofuran) material with electrochemical energy storage, which has good energy storage capacity, strong electron transmission ability, and strong charge and discharge performance. The present invention also provides a preparation method thereof, which is simple to operate and has controllable thickness. The prepared poly (3-bromofuran) material is applied to capacitor electrodes to improve the electrical performance of the electrodes.

[0005] The preparation method of the poly (3-bromofuran) material with electrochemical energy storage disclosed by the present invention comprises the following steps: dissolving tetrabutylammonium boron tetrafluoride in a mixed solution of acetonitrile and boron trifluoride etherate, and then adding 3-bromofuran to obtain an electrochemical polymerization solution; and depositing the electrochemical polymerization solution on the ITO electrode by a constant potential polymerization method in a one-chamber three-electrode system, using an ITO electrode as a working electrode, Ag / AgCl as a reference electrode, and a Pt electrode as a counter electrode, to obtain the poly (3-bromofuran) material with electrochemical energy storage.

[0006] The volume ratio of acetonitrile to boron trifluoride ether in the mixed solution is 5:1 to 4:1.

[0007] After the tetrabutylammonium boron tetrafluoride is dissolved in the mixed solution, the concentration of the tetrabutylammonium boron tetrafluoride is 0.1-0.2 mol / L.

[0008] The concentration of 3-bromofuran in the electrochemical polymerization solution is 0.1-0.2 mol / L.

[0009] In the constant potential polymerization method, the potential is 1.5-1.6V and the electrochemical deposition time is 30-40s.

[0010] In the constant potential polymerization method, the deposition area is 1.00~1.50cm 2 The interval between the three electrodes is 0.5~0.7cm.

[0011] The ITO electrode is pretreated by cutting the ITO conductive glass into 0.7 cm × 5 cm sizes with a glass cutter, and then ultrasonically cleaning it with ethanol, acetone, and ultrapure water for 10 to 15 minutes. The ITO conductive surface is then measured with a multimeter, and then it is immersed in isopropyl alcohol and deionized water in turn, and finally dried in air.

[0012] Before adopting the constant potential polymerization method, argon gas is first introduced into the electrochemical polymerization solution for 5 to 10 minutes, and the argon gas pressure is maintained at 0.13 MPa to 0.15 MPa during the constant potential polymerization process.

[0013] A poly (3-bromofuran) material with electrochemical energy storage is prepared by the preparation method of the poly (3-bromofuran) material with electrochemical energy storage.

[0014] An application of the poly(3-bromofuran) material with electrochemical energy storage: the prepared poly(3-bromofuran) material with electrochemical energy storage is used to prepare a supercapacitor electrode material.

[0015] Specifically, the method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps:

[0016] (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water ultrasonically for 10 to 15 minutes, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water in turn, and finally dry it in air.

[0017] (2) Tetrabutylammonium boron tetrafluoride is dissolved in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 5:1~4:1), with the concentration of tetrabutylammonium boron tetrafluoride being 0.1~0.2 mol / L, and then 3-bromofuran is added to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.1~0.2 mol / L.

[0018] (3) In a one-chamber three-electrode system, an ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and a Pt electrode was used as the counter electrode. A constant potential polymerization method was used. Argon was first introduced into the electrochemical polymerization solution for 5–10 min, and the argon pressure was maintained at 0.13 MPa–0.15 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.5–1.6 V, an electrochemical deposition time of 30–40 s, and a deposition area of ​​1.00–1.50 cm. 2 , the interval between the three electrodes is 0.5~0.7cm, and a poly (3-bromofuran) material with electrochemical energy storage is obtained.

[0019] The reference electrode is first prepared by polishing a 0.5 mm diameter Ag wire with sandpaper until it is smooth, and burning a 0.3 mm diameter Pt wire with an open flame until it turns red. The treated Ag wire is then connected to the working electrode, and the treated Pt wire is connected to the reference electrode. Electrolysis is carried out in a 6 mol / L hydrochloric acid solution at a constant potential of 1.5 V for 100 s. When a uniform AgCl coating layer is generated on the surface of the Ag wire, the silver plating is completed, and the silver-plated electrode Ag / AgCl is used as a reference electrode.

[0020] Furan has weak aromaticity and is highly acid-sensitive, easily inducing ring-opening reactions during electrochemical polymerization. Polyfuran prepared in conventional polymerization solutions such as acetonitrile exhibits numerous defects in its conjugated structure, and the synthesis conditions are extremely harsh. To achieve the electrochemical polymerization of poly(3-bromofuran), the present invention utilizes a potentiostatic polymerization method in a mixed solution of tetrabutylammonium boron tetrafluoride in acetonitrile and boron trifluoride etherate (V:acetonitrile:V:boron trifluoride etherate = 5:1) to prepare a poly(3-bromofuran) material with high electrochemical performance. Boron trifluoride etherate exhibits excellent ionic conductivity in the polymerization solution and, as a supporting electrolyte, also acts as an electrocatalyst. Mixing it with acetonitrile reduces the acidity of the boron trifluoride etherate, preventing ring-opening and overoxidation of the polyfuran, thereby reducing structural defects in the resulting poly(3-bromofuran).

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The poly(3-bromofuran) material prepared by the present invention has good energy storage capacity, good electrochemical properties, excellent electron transport capacity and good charge and discharge performance. It is used as an electrode for constructing a supercapacitor, improves its performance, and provides the possibility for energy storage devices with high power and high energy density.

[0023] (2) The preparation method of the poly(3-bromofuran) material for electrochemical energy storage of the present invention has controllable thickness or quality of the prepared poly(3-bromofuran) electrode material, the material is firmly attached to the electrode, and the experimental method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron micrograph of the poly(3-bromofuran) prepared in Example 1;

[0025] Figure 2 The raw material 3-bromofuran (a) and the poly (3-bromofuran) (b) prepared in Example 1 1 H-NMR spectrum.

[0026] Figure 3 The infrared spectra of the raw material poly(3-bromofuran) (a) and 3-bromofuran (b) prepared in Example 1;

[0027] Figure 4 UV-visible spectra of the raw material 3-bromofuran (a) and the poly (3-bromofuran) (b) prepared in Example 1;

[0028] Figure 5 The fluorescence emission and excitation spectra of poly (3-bromofuran) prepared in Example 1 are shown;

[0029] Figure 6 Cyclic voltammetry curves of poly(3-bromofuran) prepared in Example 1 at different scan rates in an acetonitrile solution containing tetrabutylammonium boron tetrafluoride (a) and concentrated sulfuric acid (b), as well as a linear relationship graph in acetonitrile (a-1) and a linear relationship graph in concentrated sulfuric acid (b-1);

[0030] Figure 7 This is a charge and discharge curve diagram of poly (3-bromofuran) prepared in Example 1 at different current densities. DETAILED DESCRIPTION

[0031] The present invention will be further described below with reference to specific embodiments.

[0032] The 3-bromofuran raw material used in the following examples and comparative examples was purchased from Beijing AccelaChemBio Co., Ltd. (produced by Shaoyuan Chemical Technology (Shanghai) Co., Ltd.).

[0033] The general structural formula of the prepared poly (3-bromofuran) material is , n is 15-16.

[0034] The preparation process of the reference electrode used below is as follows: first, a 0.5 mm diameter Ag wire is polished with sandpaper until smooth, and a 0.3 mm diameter Pt wire is burned with an open flame until it turns red. Then, the treated Ag wire is connected to the working electrode, and the treated Pt wire is connected to the reference electrode. Electrolysis is carried out in a 6 mol / L hydrochloric acid solution at a constant potential of 1.5 V and 100 s. When a uniform AgCl coating is formed on the surface of the Ag wire, after the silver plating is completed, the silver-plated electrode Ag / AgCl is used as the reference electrode.

[0035] Example 1

[0036] The method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps:

[0037] (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water ultrasonically for 10 minutes, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water in turn, and finally dry it in air.

[0038] (2) Tetrabutylammonium boron tetrafluoride was dissolved in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 5:1) to make the concentration of tetrabutylammonium boron tetrafluoride 0.1 mol / L, and then 3-bromofuran was added to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.1 mol / L.

[0039] (3) In a one-chamber three-electrode system, an ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and a Pt electrode was used as the counter electrode. A constant potential polymerization method was used. Argon was first introduced into the electrochemical polymerization solution for 6 minutes, and the argon pressure was maintained at 0.13 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.5 V, an electrochemical deposition time of 35 seconds, and a deposition area of ​​1.00 cm. 2 The distance between the three electrodes was 0.5 cm, and the poly (3-bromofuran) material with electrochemical energy storage was obtained, with a conductivity of 0.53 S cm -1 .

[0040] Example 2

[0041] The method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps:

[0042] (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water ultrasonically for 12 minutes, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water in turn, and finally dry it in air.

[0043] (2) Dissolve 0.15 mol / L tetrabutylammonium boron tetrafluoride in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 4.5:1) to make the tetrabutylammonium boron tetrafluoride 0.15 mol / L, and then add 3-bromofuran to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.15 mol / L.

[0044] (3) In a one-chamber three-electrode system, an ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and a Pt electrode was used as the counter electrode. A constant potential polymerization method was used. Argon was first introduced into the electrochemical polymerization solution for 5 minutes, and the argon pressure was maintained at 0.14 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.55 V, an electrochemical deposition time of 30 seconds, and a deposition area of ​​1.20 cm. 2 The distance between the three electrodes was 0.6 cm, and the poly (3-bromofuran) material with electrochemical energy storage was obtained, with a conductivity of 0.27 S cm -1 .

[0045] Example 3

[0046] The method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps:

[0047] (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water ultrasonically for 15 minutes, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water in turn, and finally dry it in air.

[0048] (2) Tetrabutylammonium boron tetrafluoride was dissolved in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 4:1) to make the concentration of tetrabutylammonium boron tetrafluoride 0.2 mol / L, and then 3-bromofuran was added to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.2 mol / L.

[0049] (3) In a one-chamber three-electrode system, an ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and a Pt electrode was used as the counter electrode. A constant potential polymerization method was used. Argon was first introduced into the electrochemical polymerization solution for 10 min, and the argon pressure was maintained at 0.15 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.6 V, an electrochemical deposition time of 40 s, and a deposition area of ​​1.50 cm. 2 The distance between the three electrodes was 0.7 cm, and the poly (3-bromofuran) material with electrochemical energy storage was obtained with a conductivity of 0.12 S cm -1 .

[0050] Comparative Example 1

[0051] This comparative example is the same as Example 1, except that the "mixed solution of acetonitrile and boron trifluoride etherate (volume ratio 5:1)" in step (2) is replaced with "boron trifluoride etherate solution". The conductivity of the obtained material is 0.085S cm -1 .

[0052] Comparative Example 2

[0053] This comparative example is the same as Example 1, except that the "mixed solution of acetonitrile and boron trifluoride ether (volume ratio 5:1)" in step (2) is replaced by "acetonitrile solution". The conductivity of the obtained material is 0.035S cm -1 .

[0054] Comparative Example 3

[0055] This comparative example is the same as Example 1, except that the tetrabutylammonium boron tetrafluoride in step (2) is removed. The conductivity of the obtained material is 0.042S cm -1 .

[0056] The poly (3-bromofuran) material with electrochemical energy storage prepared in Example 1 above was subjected to structural and morphological characterization, spectral characterization, and electrochemical energy storage performance characterization.

[0057] (1) Scanning electron microscopy (SEM) was performed on the poly (3-bromofuran) prepared in Example 1. The scanning results are as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of the prepared polymer film is smooth and compact, showing a granular structure. This structure facilitates the easier entry and exit of doped anions in the polymer film during the doping and dedoping process, increasing the electron transfer efficiency and thus improving the electrochemical performance. The conductivity of the prepared poly (3-bromofuran) was measured by the four-electrode method to be 0.53S cm -1 .

[0058] (2) 3-bromofuran and poly (3-bromofuran) prepared in Example 1 were subjected to1 H-NMR characterization, nuclear magnetic hydrogen spectrum such as Figure 2 As shown, Figure 2 (a) is the raw material 3-bromofuran 1 H-NMR spectrum, (b) is the poly (3-bromofuran prepared in Example 1 1 H-NMR spectrum, by Figure 2 It can be seen that the proton chemical shift of δ6.46 is attributed to the proton at the C(4) position. This chemical shift shifts to the downfield in the spectrum of poly(3-bromofuran), indicating that the C–H bond at the C(4) position still exists in the polymer, that is, C(4) is not a polymerization site. The proton chemical shift at 7.39 ppm can be attributed to C(2) and C(5). This proton chemical shift disappears in the H NMR spectrum of poly(3-bromofuran), indicating that the 3-bromofuran monomer forms a new bond through the C(2) and C(5) bonds. H NMR spectrum analysis confirmed that the polymerization of 3-bromofuran occurred at the C(2) and C(5) positions.

[0059] (III) The poly (3-bromofuran) prepared in Example 1 was subjected to infrared spectroscopy scanning. The scanning graph is shown in FIG. Figure 3 As shown, Figure 3 a is the infrared spectrum of the raw material 3-bromofuran, b is the infrared spectrum of the poly (3-bromofuran) prepared in Example 1, Figure 3 It can be seen that the spectrum of poly (3-bromofuran) is relatively broad, mainly because the polymer has a wide molecular chain distribution. -1 , 1400cm -1 and 1083cm -1 The stretching vibration of the furan aromatic ring is shown at 3116 cm -1 The disappearance of the absorption peak at 805 cm -1 The presence of the absorption peaks confirms the existence of α-α´ coupling, indicating that the polymerization occurs at C(2) and C(5). At the same time, the 820cm -1 and 730cm -1 This is also confirmed by the disappearance of the absorption peak in the polymer, and infrared spectroscopy analysis further confirmed that the polymerization of 3-bromofuran occurred at the C(2) and C(5) positions.

[0060] (IV) The poly (3-bromofuran) prepared in Example 1 was characterized by UV-visible spectroscopy. The UV-visible absorption spectra of 3-bromofuran and poly (3-bromofuran) are as follows: Figure 4 As shown, Figure 4 a is the UV-visible spectrum of the raw material 3-bromofuran, b is the UV-visible spectrum of the poly (3-bromofuran) prepared in Example 1, Figure 4It can be seen that 3-bromofuran monomer exhibits a characteristic absorption at 208 nm. In contrast, the UV-visible spectrum of the poly(3-bromofuran) film shows a broad absorption in the 340-600 nm range, with a more pronounced absorption at 463 nm. The longer the wavelength of the absorption peak, the longer the conjugated chains in the polymer. The broad UV-visible spectrum indicates that poly(3-bromofuran) has a wide molecular weight distribution.

[0061] (V) Fluorescence spectrum characterization of poly (3-bromofuran) prepared in Example 1. The fluorescence spectrum of poly (3-bromofuran) is as follows: Figure 5 As shown. Figure 5 As can be seen, a distinct broad excitation spectrum peak exists in the 300nm range. Simultaneously, the emission spectrum is primarily concentrated at 430nm. Furthermore, the poly(3-bromofuran) film exhibits high fluorescence intensity. The broad excitation and emission spectra are attributed to the broad molecular weight distribution of poly(3-bromofuran). The excitation and emission spectra of poly(3-bromofuran) exhibit a significant shift toward longer wavelengths compared to those of 3-bromofuran monomer, consistent with its strong electron delocalization effect. These results demonstrate that poly(3-bromofuran) is an excellent blue-light luminescent material with potential applications in a wide range of fields.

[0062] (VI) The electrochemical performance of poly(3-bromofuran) prepared in Example 1 was characterized. The cyclic voltammetry curves of poly(3,4-dibromothiophene) prepared in pure boron trifluoride ether in acetonitrile (a) and concentrated sulfuric acid (b) are shown in FIG. Figure 6 As shown in a and b, Figure 6 a-1 is the linear relationship diagram in acetonitrile, b-1 is the linear relationship diagram in concentrated sulfuric acid, scanning rate: 25mVs −1 , 50mVs −1 , 100mVs −1 , 150mVs −1 , 200mVs −1 , 250mVs −1 .Depend on Figure 6 It can be seen that the steady-state cyclic voltammetry exhibits a broad redox peak, and the maximum current density jpa and jpc are closely related to the voltage scan rate (range 25-250 mV s -1 ) into a good linear relationship (such as Figure 6(shown in a-1 and b-1). The good linear relationship between scan rate and peak current density indicates that the polymer film is well anchored to the electrode. For an electrode material, when the peak current density is proportional to the square root of the scan rate, the redox reaction is diffusion-controlled, i.e., a cell process. However, when the redox process is non-diffusion-controlled, the peak current density is proportional to the scan rate, indicating a capacitive redox process. Therefore, the reversible redox behavior of the poly(3-bromofuran) material is non-diffusion-controlled, demonstrating the pseudocapacitive properties of the prepared poly(3-bromofuran) material.

[0063] Depend on Figure 6 It can be seen that poly(3-bromofuran) can be oxidized and reduced in the range of 0.63V and 1.43V in acetonitrile solution containing tetrabutylammonium boron tetrafluoride. However, in concentrated sulfuric acid, poly(3-bromofuran) can oxidize and reduce the polymer film in a narrower potential range (from 0.33V to 0.83V). The difference between the oxidation and reduction peak potentials of poly(3-bromofuran) is 0.09V in concentrated sulfuric acid and 0.31V in acetonitrile solution. From these results, it can be seen that the doping-undoping reaction of poly(3-bromofuran) in concentrated sulfuric acid is faster than that in acetonitrile solution, which is mainly due to the different doping anions and polymer protonation. On the one hand, the doping anions in concentrated sulfuric acid (HSO4 - or SO4 2- )) than the conductive anion BF4 in acetonitrile solution containing tetrabutylammonium boron tetrafluoride - The presence of concentrated sulfuric acid facilitates the transfer of dopant anions into and out of the polymer membrane. Furthermore, concentrated sulfuric acid increases the proton concentration of the solution during cyclic voltammetry scans, leading to rapid proton transfer from the reaction zone to the bulk solution. This high proton concentration may also cause protonation and deprotonation of the membrane during the doping and dedoping process. Therefore, the exchange of dopant anions in and out of the poly(3-bromofuran) membrane is faster in concentrated sulfuric acid than in acetonitrile, indicating that the prepared poly(3-bromofuran) possesses excellent redox reversibility.

[0064] (VII) The capacitance performance of the poly(3-bromofuran) prepared in Example 1 was characterized. The constant current charge-discharge curves of the poly(3-bromofuran) were tested at different current densities (5A, 10A, 15A, 20A, and 25A) in an acetonitrile solution containing tetrabutylammonium boron tetrafluoride. Figure 7 As shown. Figure 7 It can be seen that the redox characteristics of the poly (3-bromofuran) material in the charge and discharge process are approximately triangular, indicating that its pseudocapacitive characteristics are good. The specific capacitance of the poly (3-bromofuran) material was calculated using the charge and discharge curve. At a current density of 5Ag -1 At a current density of 1.5 GHz, the maximum specific capacitance of poly(3-bromofuran) material is 83.8 Fg -1 When the current density increases to 25Ag-1 When the material has a specific capacitance of 43.7Fg -1 . The capacitance retention rate of the poly (3-bromofuran) material is 52.1%, indicating that the prepared poly (3-bromofuran) material has good rate performance. However, with the increase of current density, the specific capacitance of the material gradually decreases. The reason is that when the current density is low, the dopant ions have enough time to embed into and extract the poly (3-bromofuran) electrode. At higher current density, the diffusion of the dopant ions is not sufficient, and the degree of contact between the dopant ions and the electrode material is low, resulting in a decrease in the specific capacitance of the poly (3-bromofuran) material at higher current density. This result shows that the prepared poly (3-bromofuran) material has good electrochemical energy storage performance.

Claims

1. A method for preparing a poly (3-bromofuran) material having electrochemical energy storage, characterized in that: The following steps are involved: Tetrabutylammonium boron tetrafluoride is dissolved in a mixed solution of acetonitrile and boron trifluoride ether, and 3-bromofuran is added to obtain an electrochemical polymerization solution; In a one-chamber three-electrode system, an ITO electrode is used as a working electrode, Ag / AgCl is used as a reference electrode, and a Pt electrode is used as a counter electrode. A constant potential polymerization method is adopted to deposit an electrochemical polymerization solution on the ITO electrode to obtain a poly(3-bromofuran) material with electrochemical energy storage. The volume ratio of acetonitrile to boron trifluoride ether in the mixed solution is 5:1-4:

1. The conductivity of the poly(3-bromofuran) material with electrochemical energy storage is ≥0.1S cm -1 The general structural formula of the prepared poly (3-bromofuran) material is , n is 15-16.

2. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: After the tetrabutylammonium boron tetrafluoride is dissolved in the mixed solution, the concentration of the tetrabutylammonium boron tetrafluoride is 0.1-0.2 mol / L.

3. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: The concentration of 3-bromofuran in the electrochemical polymerization solution is 0.1-0.2 mol / L.

4. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: In the constant potential polymerization method, the potential is 1.5-1.6V and the electrochemical deposition time is 30-40s.

5. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 4, characterized in that: In the constant potential polymerization method, the deposition area is 1.00~1.50cm 2 , the interval between the three electrodes is 0.5~0.7cm.

6. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: The ITO electrode is pretreated first: the ITO conductive glass is cut into a size of 0.7 cm×5 cm with a glass cutter, and is ultrasonically cleaned with ethanol, acetone, and ultrapure water for 10 to 15 minutes in turn, and then the ITO conductive surface is measured with a multimeter, and then immersed in isopropyl alcohol and deionized water in turn, and finally dried in air.

7. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: Before the constant potential polymerization method is adopted, argon gas is introduced into the electrochemical polymerization solution for 5 to 10 minutes, and the argon gas pressure is maintained at 0.13 MPa to 0.15 MPa during the constant potential polymerization process.

8. A poly(3-bromofuran) material with electrochemical energy storage, characterized in that: The poly(3-bromofuran) material having electrochemical energy storage is prepared by the preparation method of any one of claims 1 to 7, wherein the prepared poly(3-bromofuran) material has the general structural formula: , n is 15-16.

9. An application of the poly (3-bromofuran) material with electrochemical energy storage according to claim 8, characterized in that: The prepared poly (3-bromofuran) material with electrochemical energy storage is used to prepare supercapacitor electrode material.